2017
DOI: 10.1186/s12936-016-1665-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of routinely-available, retrospective data to study the association between malaria control scale-up and micro-economic outcomes in Zambia

Abstract: BackgroundCountry-level evidence on the impact of malaria control on micro-economic outcomes is vital for mobilizing domestic and donor resources for malaria control. Using routinely available survey data could facilitate this investigation in a cost-efficient way.MethodsThe authors used Malaria Indicator Surveys (MIS) and Living Conditions Monitoring Survey (LCMS) data from 2006 to 2010 for all 72 districts in Zambia to relate malaria control scale-up with household food spending (proxy for household well-bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Despite the continued fight against high malaria endemicity for the last half-century, Zambia is among those sub-Saharan countries affected by the reported stagnation in malaria progress [6,7]. With a massive scale-up in interventions [7][8][9][10] in the last decade, Zambia achieved considerable progress, resulting in a move away from control targets to elimination aspirations [11]. Zambia embraced the currently renewed global interest for malaria elimination, and strategically positioned itself within a regional and global malaria eradication context.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the continued fight against high malaria endemicity for the last half-century, Zambia is among those sub-Saharan countries affected by the reported stagnation in malaria progress [6,7]. With a massive scale-up in interventions [7][8][9][10] in the last decade, Zambia achieved considerable progress, resulting in a move away from control targets to elimination aspirations [11]. Zambia embraced the currently renewed global interest for malaria elimination, and strategically positioned itself within a regional and global malaria eradication context.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly reported indicator using program data was the proportion of enumerated structures sprayed (per spray cycle) using spray campaign data [ 59 , 67 , 68 , 72 , 73 , 77 , 78 ]. None of the reviewed studies reported the proportion of population at risk sleeping under an ITN or living in a house sprayed by IRS in the previous 12 months, potentially due to the difficulties in translating program data to household-level ownership measures [ 81 ]. Two studies reported estimates for the proportion of the population at risk protected by IRS, using routine monitoring data [ 59 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our DHS-survey data on malaria at the individual level should be at least as good if not better than jurisdictional-level data, which necessarily rely on modeling assumptions to estimate population-level malaria rates. While greater levels of granularity are conceptually superior to aggregated data (e.g., Comfort et al, 2017), the difference in approach could account for the difference in findings.…”
Section: Discussionmentioning
confidence: 99%
“…Spatially aggregated data is potentially prone to the ecological fallacy (Piantadosi, 1988) or unmeasured confounding factors. One study of aggregated malaria survey data concluded that "it is not clear…that meaningful results can be obtained when survey data are highly aggregated; researchers…should asses the feasibility of disaggregating existing survey data" (Comfort et al, 2017). Fourth, the number of observations in previous studies is small, with fewer than 1000 observations in all but one study and fewer than 100 observations in three studies.…”
Section: Introductionmentioning
confidence: 99%